Households’ willingness-to-pay for fish product attributes and implications for market feasibility of wastewater-based aquaculture businesses in Hanoi, Vietnam - Danso, George K.; Otoo, Miriam; Duy Linh, N.; Madurangi, Ganesha (MDPI, 2017)
A choice experiment was used to assess households’ willingness-to-pay (WTP) for informational attributes (sources of water used to rear sh, and certi cation) of sh products in Hanoi, Vietnam. The study showed that households’ purchasing decisions are in uenced by their access to information of food product attributes and ascribe an economic value to it. The results indicated that households are willing to pay 51% (USD 1.11 per kg) above the prevailing market price of sh for information to know if wastewater is used to rear the sh they consume. Similarly, they are willing to pay 20% above the prevailing market price of sh (USD 0.43 per kg) to know if freshwater is used as a rearing medium. It is important to note that the increased marginal WTP is for information on whether the sh they consume is raised in wastewater over freshwater. This supports the notion of households’ concern over the safety of consuming wastewater-raised sh. Households are also willing to pay 65% (USD 1.42 per kg) above the prevailing market price for certi ed sh. Based on the cost of sh certi cation and WTP estimates, we found a total economic bene t of USD 172 million for the implementation of a wastewater-raised sh business model in Hanoi. The demand for wastewater-raised sh is likely to be affected by households’ perception of certi cation by a trusted government agency, source of water used to raise the sh, age, income and household size.